2014
DOI: 10.2965/jwet.2014.123
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Matrix Effects in Pesticides and their Transformation Product Analysis Using LC-Positive-Electronspray-MS/MS

Abstract: Liquid chromatography-triple quadrupole mass spectrometer (LC/MS/MS) using electrospray ionization (ESI) is a commonly used analytical method for environmental safety even though there are limitations to its robustness. One of the limitations, the matrix effect (ME), is defined as the ionization suppression/enhancement by the co-eluting residual component, which creates large uncertainties in quantification. The objective of this study is to address ME in the analysis of pesticides and their transformation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Takanashi et al focused on 3-methyl-4-nitrophenol (3M4NP), a typical hydrolysate of fenitrothion, and proposed that chloro-5-hydroxy-2-nitrobenzoic acid was possibly generated as a chlorination product of 3M4NP [83]. Kondo et al monitored pesticides and their transformation products in water environments utilizing LC-MS/MS [84]. Kasuga et al analyzed dissolved organic matter (DOM) in eleven major lakes in Japan water using HRMS [85].…”
Section: Approach Required To Solve the Problemmentioning
confidence: 99%
“…Takanashi et al focused on 3-methyl-4-nitrophenol (3M4NP), a typical hydrolysate of fenitrothion, and proposed that chloro-5-hydroxy-2-nitrobenzoic acid was possibly generated as a chlorination product of 3M4NP [83]. Kondo et al monitored pesticides and their transformation products in water environments utilizing LC-MS/MS [84]. Kasuga et al analyzed dissolved organic matter (DOM) in eleven major lakes in Japan water using HRMS [85].…”
Section: Approach Required To Solve the Problemmentioning
confidence: 99%
“…In order to minimize the effect of matrices on analyte recovery, dilution of the sample solution is a convenient technique. 17,19) However, Stahnke et al reported that the MME varied depending on the pesticide/matrix combination and resulted in the requirement of different dilution factors for the complete elimination of matrix effects, and extreme dilution is not acceptable due to the detectability limitation of the analyzer. 17) The combination of target pesticides and food samples can be substantially altered according to the purpose of the analysis.…”
Section: Evaluation Of Matrix Effectsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] However, matrix effects, such as ionic suppression and enhancement, can reduce analytical reliability, even that of LC-MS/MS. [14][15][16][17][18][19] Several techniques have been developed in order to deal with this problem. The matrix-matched calibration method is one technique to overcome sample matrices by mixing sample matrices from blank samples into the standard solutions.…”
Section: Introductionmentioning
confidence: 99%